Educare i minori non accompagnati: uno sguardo su un'esperienza del secondo dopoguerra - Silvia Guetta (Firenze University Press, 2017)
Looking at young immigrants coming to Italy alone from war and famine zones and human rights violations, the article seeks to put forward a number of ideas for consideration by presenting how Reuven Feuerstein, in a totally different condition and situation, programmed high quality educational experiences for unaccompanied minors. With reference to current rules regarding this particular type of immigrants, the article examines the need of clear measures of educational planning to ensure individuals' wellbeing and future of social implementation to involve the whole citizen body.